Stem cell factor restrains endoplasmic reticulum stress-associated apoptosis through c-Kit receptor activation of JAK2/STAT3 axis in hippocampal neuronal cells. - Haiying Shen; Junjie Nie; Guangqing Li; Hongyan Tian; Jun Zhang; Xiaofeng Luo; Da Xu; Jie Sun; Dongfang Zhang; Hong Zhang; Guifang Zhao; Weiyao Wang; et al. (PLoS ONE)
Background Alzheimer's disease (AD) is a common elderly disorder characterized by cognitive decline. Endoplasmic reticulum (ER) stress has been implicated in various neurodegenerative diseases, including AD. Stem cell factor (SCF) performs its biological functions by binding to and activating receptor tyrosine kinase c-Kit. We aimed to investigate the effects of SCF/c-Kit and JAK2/STAT3 on ER stress and apoptosis in AD. Methods The study employed L-glutamic acid (L-Glu)-treated HT22 cells as sporadic AD cell model and APP/PS1 mice as an animal model of familiar AD. SCF, c-Kit inhibitor ISCK03 or JAK2/STAT3 inhibitor WP1066 was treated to verify the effects of SCF/c-Kit and JAK2/STAT3 on ER stress and apoptosis of L-Glu-exposed HT22 cells. Cell viability was assessed by MTT. BrdU detected cell proliferation. Flow cytometry measured cell apoptosis. The expression levels of ER stress markers GRP78, PERK, CHOP, and apoptosis protein caspase3 were determined by western blot. The effect on the mRNA of ER stress markers GRP78, PERK, CHOP and apoptotic caspase3 were quantified by RT-qPCR in primary cultured hippocampal neurons from APP/PS1 transgenic mice. Results Administration of SCF significantly augmented the activity and proliferation of hippocampal neuronal cells, protecting cells against L-Glu induced ER stress-associated apoptosis. Moreover, the addition of ISCK03 (c-Kit inhibitor) or WP1066 (JAK2/STAT3 inhibitor) reversed SCF effects on ER stress and apoptosis in vitro. Conclusion We found that SCF inhibits L-Glu-induced ER stress-associated apoptosis via JAK2/STAT3 axis in HT22 hippocampal neuronal cells, as well as in primary hippocampal neurons from APP/PS1 mice, which provides valuable insights into the molecular mechanisms underlying the pathogenesis of AD and explores novel therapeutic targets for both sporadic and familial AD.